Development of Test Instrument TIMSS Model to Measure Mathematical Ability VIII Grade Students - Adi, Nur Romdlon Maslahul; Kartono, Kartono; Susilaningsih, Endang (Journal of Research and Educational Research Evaluation, 2019)
The teachers are still lack found practice tests that have characteristics such as the Trend in International Mathematics and Science Study (TIMSS) in Junior High School mathematics textbooks. This study aims to develop a TIMSS test instrument model that refers to the cognitive domain and the content domain for class VIII students. The respondents of this study were 5 people in the expert test, 10 people in the one to one test and 53 people in the small-scale test. This research is development research conducted following the development model of Borg & Gall. This step is only taken until the ninth step with a few modifications. Modifications are made by adding a one to one test copy from Tessmer. In content validity, as many as 5 items out of 35 items developed are not yet valid with a coefficient range of 0.6-0.79. Items were then revised to be tested in the small-scale test stage. One to one test results showed the instrument readability level was 81%. The validity test of the criteria shows a coefficient of 0.84 which means that the product developed is comparable to the original product. Interrater reliability was 0.661 and Alpha Chronbach reliability testing was a small scale at 0.854. The results showed that the instrument developed was valid in terms of content and criteria as well as reliable for use. The benefit of this research is that the developed test instrument can be used as a tool to measure the mathematics abilities of eighth-grade students.